Characterization and Ectopic Expression of CoWRI1, an AP2/EREBP Domain-Containing Transcription Factor from Coconut (Cocos nucifera L.) Endosperm, Changes the Seeds Oil Content in Transgenic Arabidopsis thaliana and Rice (Oryza sativa L.) - Sun, RuHao; Ye, Rongjian; Gao, Lingchao; Zhang, Lin; Wang, Rui; Mao, Ting; Zheng, Yusheng; Li, Dongdong; Lin, Yongjun (Frontiers in Plant Science, 2017)
Coconut (Cocos nucifera L.) is a key tropical crop and a member of the monocotyledonous family Aracaceae (Palmaceae). Few genes and related metabolic processes involved in coconut endosperm development have been investigated. In this study, a new member of the WRI1 gene family was isolated from coconut endosperm and was named CoWRI1. Its transcriptional activities and interactions with the acetyl-CoA carboxylase (BCCP2) promoter of CoWRI1 were confirmed by the yeast two-hybrid and yeast one-hybrid approaches, respectively. Functional characterization was carried out through seed-specific expression in Arabidopsis and endosperm-specific expression in rice. In transgenic Arabidopsis, high over-expressions of CoWRI1 in seven independent T2 lines were detected by quantitative real-time PCR. The relative mRNA accumulation of genes encoding enzymes involved in either fatty acid biosynthesis or triacylglycerols assembly (BCCP2, KASI, MAT, ENR, FATA, and GPDH) were also assayed in mature seeds. Furthermore, lipid and fatty acids C16:0 and C18:0 significantly increased. In two homozygous T2 transgenic rice lines (G5 and G2), different CoWRI1 expression levels were detected, but no CoWRI1 transcripts were detected in the wild type. Analyses of the seed oil content, starch content, and total protein content indicated that the two T2 transgenic lines showed a significant increase (P<0.05) in seed oil content. The transgenic lines also showed a significant increase in starch content, whereas total protein content decreased significantly. Further analysis of the fatty acid composition revealed that palmic acid (C16:0) and linolenic acid (C18:3) increased significantly in the seeds of the transgenic rice lines,but oleic acid (C18:1) levels significantly declined.